Pengembangan Kit Isolasi DNA Low-Cost dan Ramah Lingkungan untuk Berbagai Sampel - Tirtasari , Ni Luh; Eralita, Norma; Siswanti, Siswanti (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Science learning includes the study of concepts as well as practical activities. Practical science learning can run effectively when supported by adequate laboratory facilities and infrastructure. This study aims to develop a low-cost and environmentally friendly DNA isolation kit as an alternative medium for molecular biology practicum that is more affordable and easier to implement in educational laboratories. The kit development utilizes simple materials and equipment that are easily obtained from the surrounding environment, such as enzyme-based liquid detergent, table salt, natural enzyme extracts (pineapple, ginger, papaya leaves, and papain), and ethanol. The research method employed an experimental approach through stages of kit formula design, optimization of lysis buffer composition, and effectiveness testing on various plant and animal tissue samples, namely strawberry, broccoli, chicken liver, and chicken meat. The success parameters were observed through the visualization of DNA threads resulting from precipitation and the measurement of DNA quantity and purity using a spectrophotometer. The results indicate that all kit formulas were able to extract DNA with varying levels of success, where strawberry and chicken liver samples showed the clearest DNA thread visualization and the best color appearance. These findings demonstrate that a locally based, low-cost, and eco-friendly DNA isolation kit is effective as an alternative to commercial kits and has strong potential to support science learning, particularly in genetics and biotechnology, through more practical and economical laboratory activities.